Moderation Effect of Government Regulation on the Joint Influence of Water Pricing, Infrastructure Financing, Utility Efficiency and Subsidies on Financial Sustainability of Water Service Providers in Kenya - Julius, Christine Mawia; Okech, Timothy C. (International Journal of Economics and Financial Issues, 2021)
The purpose of the study was to examine the moderating effect of government regulation on the joint influence of water pricing, infrastructure financing, utility efficiency and subsidies on financial sustainability of Water Service Providers (WSPs) in Kenya. It adopted pragmatism research philosophy using explanatory sequential mixed design, while targeting a population of 616 and a sample of 352 respondents comprising of senior managers from eighty-eight registered WSPs in Kenya. Quantitative data was collected using a structured questionnaire; additional data was collected using interview schedule administered on key informants. Data collected, was coded, cleaned and analyzed to obtain both descriptive and inferential statistics. A two-step regression analysis and analysis of variance (ANOVA) was carried out to establish the nature and the magnitude of hypothesized relationships. The results showed that government regulation has a positive and significant moderating effect on the joint influence of water pricing, infrastructure financing, utility efficiency and subsidies on financial sustainability of WSPs in Kenya. Unlike many studies which have focused on the demand side, this study focused on the supply side and revealed that financial sustainability is a product of many factors which government policy must address concomitantly thus calling for implementation of integrated water management policies. Keywords: Government Regulation, Water Pricing, Financial Sustainability, Infrastructure Financing, Utility Efficiency, Subsidies JEL Ð¡lassÑ–fÑ–catÑ–ons: Q01, Q25, Q28 DOI: https://doi.org/10.32479/ijefi.11443